2022
DOI: 10.3920/bm2021.0123
|View full text |Cite
|
Sign up to set email alerts
|

Comparing probiotic and drug interventions in irritable bowel syndrome: a meta-analysis of randomised controlled trials

Abstract: Clinical decisions made by health professionals to recommend either drug or probiotic interventions for irritable bowel syndrome (IBS) should be supported by proper knowledge of the efficacy rates of both types of interventions. In this article, we performed a systematic review and meta-analysis to examine the efficacy of both probiotic- and drug interventions in IBS. Medline was searched between January 2015 – January 2021. Randomised controlled trials (RCT) recruiting participants > 18 years old with IBS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…From the results of the study, table 2 showed that the majority or as many as 76 babies (48.1%) experienced an increase in NH on the first to second day. These results are in line with research Van der Geest et al, (2022) which states that the majority of neonatal population samples experiencing NH will experience a yellow manifestation after 24 hours. This theory is also in line with research Thielemans et al, (2021) which stated a significant association between an increase in neonatal bilirubin levels at 48 hours of neonatal life and the incidence of NH (P = 0.009)…”
Section: Univariate Discussionsupporting
confidence: 91%
“…From the results of the study, table 2 showed that the majority or as many as 76 babies (48.1%) experienced an increase in NH on the first to second day. These results are in line with research Van der Geest et al, (2022) which states that the majority of neonatal population samples experiencing NH will experience a yellow manifestation after 24 hours. This theory is also in line with research Thielemans et al, (2021) which stated a significant association between an increase in neonatal bilirubin levels at 48 hours of neonatal life and the incidence of NH (P = 0.009)…”
Section: Univariate Discussionsupporting
confidence: 91%
“…Details of many older trials that are not the focus of the current review can be found in that report. At least six systematic reviews have since been published on probiotics in IBS, examining the effects of probiotics at different levels of specificity [23 ▪ –28 ▪ ]; the considerable variation in reported effectiveness between different genera, species and strains is summarized in Table 1.…”
Section: Irritable Bowel Syndromementioning
confidence: 99%
“…These meta-analyses found that, when analysed globally across all probiotics, overall they led to beneficial impacts on global symptoms, abdominal pain and bloating in IBS patients [25 ▪ ,27 ▪ ]. However, aggregating the effects of different probiotics into a meta-analysis should be undertaken with caution as different probiotics have different characteristics that will inevitably impact on their efficacy.…”
Section: Irritable Bowel Syndromementioning
confidence: 99%
“…The CONSORT Statement offers a standard way for authors to prepare reports of trial findings, facilitating their complete and transparent reporting, and aiding their critical appraisal and interpretation. Hence, this tandem publication aimed to determine both efficacy (Van der Geest et al, 2022) and safety (this article) of RCTs, contributing to an assessment of a burden to benefit ratio to substantiate medical decisions. This article will determine safety profiles by analysing the AEs reported in RCTs.…”
Section: Inadequate Safety Reporting In the Publications Of Randomise...mentioning
confidence: 99%